2017
DOI: 10.1016/j.dld.2017.01.168
|View full text |Cite
|
Sign up to set email alerts
|

Early management of acute pancreatitis: A review of the best evidence

Abstract: In the 20th century early management of acute pancreatitis often included surgical intervention, despite overwhelming mortality. The emergence of high-quality evidence (randomized controlled trials and meta-analyses) over the past two decades has notably shifted the treatment paradigm towards predominantly non-surgical management early in the course of acute pancreatitis. The present evidence-based review focuses on contemporary aspects of early management (which include analgesia, fluid resuscitation, antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 89 publications
0
73
0
10
Order By: Relevance
“…The importance of fluid therapy in acute pancreatitis cannot be overstressed and has been shown in several studies, as well as its relation to the development of complications (Stigliano et al 2017). In this particular setting, literature has not been consensual, avoiding to give strict indications on the volume to administer because the results are quite disparate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of fluid therapy in acute pancreatitis cannot be overstressed and has been shown in several studies, as well as its relation to the development of complications (Stigliano et al 2017). In this particular setting, literature has not been consensual, avoiding to give strict indications on the volume to administer because the results are quite disparate.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive fluid therapy (infusion of high fluid volumes) seems to contribute to the maintenance of the microcirculation (Janisch and Gardner, 2016). On the other hand, it produces excess volume in the extracellular space which also contributes to the development of complications (Stigliano, Sternby, de Madaria, Capurso, and Petrov, 2017). We are far from knowing all the factors that lead to complications that worsen the course of acute pancreatitis.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Opioids had been reported in the past study as a trigger of spasm of the sphincter of Oddi but in a recent Cochrane review on five RCTs with a total of 227 patients showed no difference between opioids and other analgesic options regarding the risk of complications or clinically serious adverse events [26]. A meta-analysis that was made by Stigliano et al concluded there was no credible evidence to avoid the use of morphine in managing pain in acute pancreatitis [28].…”
Section: Analgesicsmentioning
confidence: 99%
“…Fluid migrating from the intravascular space thus does not leave the body but is re‐distributed. A detailed more general review of management of AP has been recently published …”
Section: Introductionmentioning
confidence: 99%